SONG FOR TEACHING ENGLISH VOCABULARIES IN THE FOURTH GRADE STUDENTS - Gita, Ananda Indah; Wedhanti, N.K.; Budiarta, L.G. Rahayu (Universitas Pendidikan Ganesha, 2021)
There are some problems when the teacher teaches vocabulary. Many students have difficulty learning English. Several factors make some words difficult for students, such as pronunciation, spelling, length, complexity, meaning, range. This has an impact on the students' English ability, which is low. The purpose of this study is to analyze the activities of teaching English vocabulary to fourth-grade students. This type of research is qualitative using a qualitative descriptive method. The subjects of this study were teachers and 29 students of class IV. The methods used to collect data are observation, interviews, and questionnaires. The instruments used to collect data are observation sheets and questionnaires. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results of this study are the teaching of vocabulary used by the teacher in this study, namely alphabet songs, objects, songs of the day, songs of the month The most frequently used songs are alphabet songs. The teacher applies the alphabet song at the beginning or end of the lesson. The most enjoyable teaching song is the Alphabet song. Students are critical in learning English when the teacher implements this song. Therefore, the teacher's role is critical in choosing songs that can be used to teach them according to students' needs and preferences.